(3GdTQcI GdbGHVI hCMcGegG aj Gdabg GdESdGej (B/s - (3GdUjaj, YHO Gddg Ydj eMehOs ((3YeGf(B: s (3OGQ GdfaGFS(B, s, 2006)
(3GdJYQja HGdTQcI GdbGHVI(B-(3fTCI GdTQcI GdbGHVI(B-(3GdJCUjd Gdabgj ddTQcI GdbGHVI hGdCMcGe GdTQYjI GdeJYdbI HgG(B-(3GdCgejI GdEbJUGOjI ddTQcI GdbGHVI(B-(3eTQhY ebJQM ddTQcI GdbGHVI GdESdGejIs
Keywords: (3GdTQcI GdbGHVI GdESdGejIs; (3GdTQcIGdbGHVIs